2015
DOI: 10.1002/pola.27809
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(n‐butyl acrylate) homopolymer and poly(styrene‐bn‐butyl acrylate‐b‐styrene) triblock copolymer via AGET emulsion ATRP using a cationic surfactant

Abstract: Cationic emulsions of triblock copolymer particles comprising a poly(n-butyl acrylate) (P n BA) central block and polystyrene (PS) outer blocks were synthesized by activator generated by electron transfer (AGET) atom transfer radical polymerization (ATRP). Difunctional ATRP initiator, ethylene bis(2-bromoisobutyrate) (EBBiB), was used as initiator to synthesize the ABA type poly(styrene-b-n-butyl acrylate-b-styrene) (PS-P n BA-PS) triblock copolymer. The effects of ligand and cationic surfactant on polymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The synthesis of block copolymers composed of butyl acrylate (BA) and styrene by RAFT polymerization has been attracting great interest over the past two decades , because of the promising properties of the potentially formed materials. However, the synthesis of such block copolymers has been demonstrated to be a significant challenge, and most of the reported strategies result in broad MWDs ( Đ > 2), ,,, which are associated with chain transfer reactions inducing polymer branching. In the present system, when pure BA monomer was used in the second polymerization cycle, unsatisfactory results were obtained in terms of low conversion (Table SI4 and Figure SI5).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of block copolymers composed of butyl acrylate (BA) and styrene by RAFT polymerization has been attracting great interest over the past two decades , because of the promising properties of the potentially formed materials. However, the synthesis of such block copolymers has been demonstrated to be a significant challenge, and most of the reported strategies result in broad MWDs ( Đ > 2), ,,, which are associated with chain transfer reactions inducing polymer branching. In the present system, when pure BA monomer was used in the second polymerization cycle, unsatisfactory results were obtained in terms of low conversion (Table SI4 and Figure SI5).…”
Section: Resultsmentioning
confidence: 99%
“…By measuring the fraction of living chains at different stages of polymerisation (using a GPC dual detection method), it became evident that a significant quantity of dead chains formed during the early A rigorous study into a range of ligands and surfactants for AGET ATRP was performed by Xue et al for the synthesis of PSt-b-P n BuA-b-PSt using a difunctional ATRP initiator. 98 The authors concluded that the most hydrophobic ligand (BPMODA), which partitioned less into the aqueous phase, controlled polymerisation best (lower Đ). The surfactant cetyltrimethylammonium bromide (CTAB) provided optimal colloidal stability without interfering with polymerisation control due to its superior stability at higher temperature.…”
Section: 131mentioning
confidence: 99%